2019
DOI: 10.1177/1687814018816878
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation method for green logistics system design of agricultural products: A case study in Shandong province, China

Abstract: Recently, the environmental issue caused by logistics of agricultural products has attracted a great deal of attention. In order to solve the problem, much of work focuses on green logistics to decrease environmental pollution. However, the green logistics evaluation system of agricultural products is insufficient. Therefore, establishing a reasonable green logistics evaluation system for agricultural products plays a key role in the development of green agricultural products. In this work, domestic and intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Li et al (2020) proposed an improved analytic hierarchy process-back propagation (AHP-BP) neural network algorithm to evaluate companies' CSR performance, and results showed that this improved AHP-BP neural network model could effectively estimate CSR performance. Ni et al (2019) established a green index system and quantitatively evaluated the environmental quality of Guizhou geological parks based on the fuzzy comprehensive evaluation system. The subjective method can determine the importance of the evaluation index according to expert experience.…”
Section: Evaluation Of Environmental Responsibilitymentioning
confidence: 99%
“…Li et al (2020) proposed an improved analytic hierarchy process-back propagation (AHP-BP) neural network algorithm to evaluate companies' CSR performance, and results showed that this improved AHP-BP neural network model could effectively estimate CSR performance. Ni et al (2019) established a green index system and quantitatively evaluated the environmental quality of Guizhou geological parks based on the fuzzy comprehensive evaluation system. The subjective method can determine the importance of the evaluation index according to expert experience.…”
Section: Evaluation Of Environmental Responsibilitymentioning
confidence: 99%
“…Zhang et al (2017) developed a quantitative risk assessment method to assess the condition of the fresh agricultural products cold chain process [32]. Second, in order to solve the environmental issue caused by logistics of agricultural products, Ni et al (2019) established a scientific and reasonable agricultural products green logistics evaluation system [33]. What's more, Zhang et al (2016) and Sheng (2014) studied evaluation of regional logistics competitiveness and technical efficiency measurement respectively using the panel data of 31 provinces [34,35].…”
Section: Logistics Assessmentmentioning
confidence: 99%
“…Herold and Lee [64] investigated the carbon reports disclosed by some giant international logistics enterprises, e.g., UPS, FedX and DHL, and compared their sustainability-related strategies, namely legitimacy-seeking arguments versus energy and emission reduction. In addition, a variety of qualitative analysis measures, such as fuzzy multi-criteria evaluation modeling [65], data envelopment analysis [66], and analytic hierarchy processes [67] were also widely applied to illuminate the logic between SEE performance and G&SL.…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%